STRATEGI PEMASARAN MENGGUNAKAN WHATSAPP BISNIS PADA LATHIFA SHOP - Zuhria Miftahul Azizah (Jurnal Valuasi: Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2023)
This research is motivated by the needs of online shop owners for knowledge about marketing strategies. One marketing media that has recently been widely used is Whatsapp Business. The purpose of this research is to find out how the marketing strategy is using Whatsapp Business at Lathifa Shop. Lathifa Shop was chosen in this study because Lathifa Shop managed to rely on Whatsapp Business so that it earned millions of rupiah in profit per month and bonuses of up to tens of millions of rupiah. So, readers can apply it for marketing their business. This study used descriptive qualitative methods and carried out data analysis techniques of data reduction, data presentation, and writing conclusions. The result and conclusion of this research    are that Lathifa Shop uses 8 strategies in marketing efforts. The 8 strategies are setting up a Whatsapp Business profile, preparing a landing page for each product with a short link, setting up auto-replies on Whatsapp Business, collecting Whatsapp contacts, using modern technology to create Whatsapp Business status content, updating Whatsapp Business status with exciting content, creating promos on Whatsapp Business status, and interacting with potential buyers on Whatsapp Business before mentioning product prices